EXPLORE: An action to bring science and technology closer to secondary school - Nuria Torras-Melenchon; M. Dolors Grau; Josep Font-Soldevila; Josep Freixas (OmniaScience, 2015)
This paper presents the experience of an initiative, the EXPLORE courses, designed to bring science and technology closer to secondary school and to encourage scientific and technological vocations. The EXPLORE courses, organised by "EXPLORATORI dels Recursos de la Natura" project, are particularly addressed to secondary school teachers and are conducted at Catalonia (north-east of Spain). The main objective is to provide secondary school teachers with the opportunity to explore the natural resources. Based on a combination of face-to-face and online learning, the programme of the courses uses an interdisciplinary approach, integrating science, technology, engineering, and mathematics (STEM) and STEAM (STEM + art) fields. Data presented in this paper correspond to the 2012 and 2013 editions. The results, which were obtained from a written questionnaire completed by participating teachers of EXPLORE courses, indicate that more than 70% of secondary school teachers were encouraged to introduce some course contents on their teaching classes after participating in an EXPLORE course.